Principles of Ice Cream Cone Production in an Islamic Economic Perspective in Pacitan Home Industries - Fitrandawati, Erika (CV. Civiliza Publishing, 2024)
Introduction/Main Objectives: This research aims to determine ice cream cones' production and production principles